LA NFLUENCIA DE LOS MEDIOS DE COMUNICACIÓN SOCIAL EN LOS PROCESOS SOCIALES - Angelova, Slavyanka (Europa del Este Unida, 2021)
Social media is a result of the development of information and communication technology and web area. The multidimensional interaction through them led to the development of specific social relations and the creation of new social morphology of modern societies. It is essential to note that the ways social change has been identified have varied greatly in the history. Globalization, network connection and the influence of media are typical for modern societies. Social process and social interaction are interrelated, it is difficult to find boundaries between them therefore we have to explore and discover the causal relations.